Testicular Germ Cell Tumors in Boys <10 Years: Results of the Protocol MAHO 98 in Respect to Surgery and Watch & Wait Strategy - Göbel, U.; Haas, R.; Calaminus, G.; Botorek, P.; Schmidt, P.; Teske, C.; Schönberger, S.; Schneider, D. T.; Harms, D. (Klinische Pädiatrie, 2013)
In 1982 the GPOH opened the 1st protocol for germ cell tumors (GCTs) of the testis (MAHO 82). Here the results of the 5th version (MAHO 98) will be offered for boys <10 year of age.In MAHO 98 watch and wait (w&w) strategy after inguinal tumororchiectomy was widened from 2 to 10-year-old boys with YST stage IA (group I); other invasive measures were omitted. Thus the prognostic impact of a non-recommended surgery like transscrotal operation +/− conventional biopsy (group II) can be evaluated.Clinical diagnosis and staging by ultrasound and tumor marker. In blurry cases, a frozen section was recommended to confirm the diagnosis by histology intraoperatively. Indications for adjuvant chemotherapy were: YST stage IA without elevated AFP, YST stage>IA and all mixed malignant GCTs.From 1998 till 2005 128 boys <10 years with a testicular GCT were registered. Histology: YST n=76, teratoma n=46, mixed malignant GCT n=6. Tumor stage IA: n=101. All teratoma patients survive event-free. At all, only 19/82 patients with a malignant GCT received chemotherapy including 5 patients with a tumor progress after w&w (2/49 group I and 3/15 group II patients, respectively) and 1 patient (YST IIIA) with relapse after adjuvant chemotherapy. Transscrotal surgery (n=18) or tumorenucleation (n=6) remained without event. Indeed all patients survived.Prognosis of boys <10 year with a testicular GCT is excellent as ~80% will be cured by high inguinal tumororchiectomy alone. w&w is feasible and safe even after not recommended surgery if suitable follow-up is assured at least in stage IA cases.
Keywords: germ cell tumor; yolk sac tumor; teratoma; watch and wait; testicular tumor; tumororchiectomy